Vertical Integration as a Source of Hold-up - Allain, Marie-Laure; Chambolle, Claire; Rey, Patrick (Review of Economic Studies, 2016)
While vertical integration is traditionally seen as a solution to the hold-up problem, this article highlights instead that it can generate hold-up problems—for rivals. We consider a successive duopoly where downstream firms invest and then secure support from an upstream supplier. We first show that vertical integration generates ex ante incentives to create hold-up problems: an integrated supplier is willing to pre-commit itself to appropriating or dissipating part of its customer's profits, to expose the independent rival to being held-up by the other supplier, and discourage in this way the rival's investment. We then show that, even in the absence of any pre-commitment, vertical integration also creates hold-up problems ex post when degrading the quality of the support provided to one downstream firm benefits its rival. We also provide illustrations in terms of standard industrial organization models and of antitrust cases, and discuss the robustness of the insights.